Persetujuan Dinamis sebagai Sarana Optimalisasi Pelindungan Data Pribadi dan Hak atas Privasi - Masitoh Indriani; Annida Aqiila Putri (Badan Strategi Kebijakan Hukum, 2023)
Consent is one of the foundations for data processing in the Operation of Electronic Systems by government and private institutions. Implementing consent as a basis for data processing has several shortcomings, particularly as it primarily relies on individuals being aware in providing authentic consent. In practice, individuals often give consent without considering any terms and conditions. Consent obtained without knowledge of data processing can jeopardize the right to privacy and the protection of personal data. This paper examines dynamic consent as a means to optimize the protection of privacy rights. The findings indicate that the concept of dynamic consent that prioritizes its approach to Data Subjects serves as a means to optimize personal data protection. Dynamic consent can strike a balance between on the one hand, the simplicity of the consent mechanism, and, on the other hand, the personal data protection standards and the right to privacy. Formulating dynamic consent should be based on legal elements, societal practices, technological features, and the involvement of personal data protection authorities. Additionally, as a form of implementing accountability for Electronic System Organizers as data controllers or processors, an effective mechanism for resolving personal data disputes is needed. These elements, when combined, can provide optimal personal data protection.